1996
DOI: 10.1177/001872679604900206
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Organizational Politics: Prediction, Stress-Related Implications, and Outcomes

Abstract: The perceptions of organizational politics model proposed by Ferris, Russ, and Fandt (1989) was tested in this study, and reasonably strong support was found for most of the linkages in the model, including the moderating effects of control and understanding, and the mediating effects of politics between predictors and outcomes. Furthermore, politics was characterized as a potential source of stress in the work environment, contributing to our understanding of the dynamics of politics in organizations. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
314
2
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(343 citation statements)
references
References 37 publications
21
314
2
6
Order By: Relevance
“…Ferris, et al [26][27][28][29] came to the same conclusion in studying the empirical relationship between organizational politics and work anxiety and its relation to work stress. Firstly, they argue that politics and stress are both perceptual in nature.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Ferris, et al [26][27][28][29] came to the same conclusion in studying the empirical relationship between organizational politics and work anxiety and its relation to work stress. Firstly, they argue that politics and stress are both perceptual in nature.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Other studies have found support for the prediction that negative consequences of perceived politics may be moderated by individual differences, such as: perceived control over the work environment (Ferris, et al 1996), need for achievement , and self-promoting behaviour (Harrell-Cook, Ferris & Duhlebohn,. 1999).…”
Section: Politics and Politicians At Workmentioning
confidence: 98%
“…There is also support for hypothesized links between perceptions of politics and consequences for employees. Studies have found that higher levels of perceived politics are associated with reduced job satisfaction (Cropanzano, Howes, Grandey & Toth, 1997;Drory, 1993;Ferris, Frink, Galang, Zhou, Kacmar & Howard, 1996;Ferris & Kacmar, 1992;Nye & Witt, 1993;Parker et al 1995;Vigoda, 2000), lower employee morale (Voyer, 1994), reduced organizational commitment (Cropanzano et al 1997;Ferris & Kacmar, 1992;Nye & Witt, 1993;Randall, Cropanzana, Bormann & Birjulin 1999;Vigoda, 2000), and increased intentions to leave (Cropanzano et al 1997;Maslyn & Fedor, 1998;Vigoda, 2000). Voyer (1994) also found that employees with higher levels of employee somatic tension, burnout and general fatigue were more likely to perceive their work environment to be political.…”
Section: Perceptions Of Politicsmentioning
confidence: 99%
“…Outros efeitos relevantes identificados foram queda da moral, aumento da ansiedade e stress, fatores contraproducentes que evidentemente comprometem o resultado das organizações (Chang et al, 2009;Ferris, Frink, Galang, Zhou, Kacmar, & Howard, 1996).…”
Section: Autores Definiçãounclassified
“…Dependendo das experiências prévias de cada observador, metas pessoais de carreira, grupo do qual faz parte e até mesmo do gênero, um mesmo comportamento pode ser considerado político ou não (Ferris et al, 1996;Kacmar, Bachrach, Harris, & Zivnuska, 2011). O estudo da PPO parte da premissa de que aspectos atitudinais no local de trabalho são influenciados por percepções da realidade e não necessariamente da realidade por si só (Kacmar & Carlson, 1997;Bargal, 2006).…”
Section: Mensurando a Percepção De Política Na Organizaçãounclassified